Racial Categories as Resources and Constraints in Everyday Interactions: Implications for Racialism and Non-Racialism in Post-Apartheid South Africa - Whitehead, Kevin A (My University, 2013)
The anti-apartheid struggle was characterized by tensions between the opposing ideologies of non-racialism (exemplified by the Freedom Charter) and racialism (exemplified by Black Consciousness). These tensions have remained prevalent in public policies and discourse, and in the writings of social scientists, in the post-apartheid period. In this paper, I examine some ways in which issues of whether, when, and how race matters become visible in everyday interactions in South Africa, and what insights this may offer with respect to these ongoing tensions. Specifically, I employ an ethnomethodological, conversation analytic approach to examine some ways in which racial categories are treated as resources for action or constraints on action. I conclude by arguing that these findings point to the contingent and situational operation of a practical non-racialism (as well as practical racialism), and thus to the achievement of these ideologies in the moment-by-moment unfolding of interactions.
Keywords: Non-racialism; Racial categories; Interaction; South Africa; ethnomethodology; Conversation analysis